2013
DOI: 10.1155/2013/231279
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin and Collagen Differentially but Synergistically Regulate Sprout Angiogenesis of Human Dermal Microvascular Endothelial Cells in 3-Dimensional Matrix

Abstract: Angiogenesis is a highly regulated event involving complex, dynamic interactions between microvascular endothelial cells and extracellular matrix (ECM) proteins. Alteration of ECM composition and architecture is a hallmark feature of wound clot and tumor stroma. We previously reported that during angiogenesis, endothelial cell responses to growth factors are modulated by the compositional and mechanical properties of a surrounding three-dimensional (3D) extracellular matrix (ECM) that is dominated by either cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 30 publications
(36 reference statements)
3
64
0
3
Order By: Relevance
“…The cells were rearranged into thin-wall ring-shaped structures. The addition of fibrin [Wolf et al, 2009;Feng et al, 2013] was required to fill the inner opened space of the ring and increase its thickness. Supplementation of collagen1 hydrogels with fibronectin and vitronectin had no effect on ring texture or thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were rearranged into thin-wall ring-shaped structures. The addition of fibrin [Wolf et al, 2009;Feng et al, 2013] was required to fill the inner opened space of the ring and increase its thickness. Supplementation of collagen1 hydrogels with fibronectin and vitronectin had no effect on ring texture or thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen is known for greater mechanical strength, facilitating its use for mechanically loaded tissues [21]. The higher modulus of collagen is known to result in low endothelial cell sprouting compared to fibrin [19, 39]. In studies, fibrin showed a 32.4% increase in microvessel formation from ECs and a 73.5% wider vascular area than collagen [40].…”
Section: Discussionmentioning
confidence: 99%
“…Even though we have chosen to use one uniform concentration, the difference in cell behaviors and morphologies in each gel can be a result of combined characteristics such as biochemical and biomechanical cues. According to a literature, in cell-matrix interactions, αvβ3 and α5β1 integrins dominate in fibrin-based environments and α2β1 integrins dominate in collagen [19, 41]. According to Feng et al ’s study, the sprouting action of ECs was enhanced in fibrin over collagen, as determined by microbead outgrowth assay [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable and long sprouts were formed within moderate matrix density of 1.2 and 1.9 mg/ml [109]. Feng et al also demonstrated that the composition of proteins of the extracellular matrix has an effect on sprout angiogenesis [271]. Nguyen et al developed a novel microfluidic device to study the effect of angiogenic factors on angiogenesis sprouting in the presence of fluid flow in the parent vessel [272].…”
Section: Blood Vessel Formation Via Angiogenesismentioning
confidence: 99%